Comprehensive functional evaluation of the injured runner - Plastaras, C. T.; Rittenberg, J. D.; Rittenberg, K. E.; Press, J.; Akuthota, V. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
In most cases, a detailed history provides the information that is necessary for the clinician to diagnose the injured runner correctly; however, to treat the injury and guide a successful rehabilitation program, the physical examination must go beyond the standard regional musculoskeletal examination. The victims (tissue injury) and the culprits (biomechanical deficits) must be identified to facilitate treatment (Table 3). Gait and other dynamic assessments help to reveal underlying deficits in function that may have contributed to injury. In short, the entire functional kinetic chain must be considered and weak links identified.